Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

7 - 3 ( 5t - 10 ) = 67


Sagot :

D3xt3R
[tex]7-3(5t-10)=67[/tex]

[tex]7-(3*5t-3*10)=67[/tex]

[tex]7-15t-(-30)=67[/tex]

[tex]7-15t+30=67[/tex]

[tex]-15t=67-30-7[/tex]

[tex]-15t=30[/tex]

then...

[tex]t=-\frac{30}{15}[/tex]

[tex]\boxed{\boxed{t=-2}}[/tex]
Answer in an annex
....................................
View image tomek1172